Mutual Support Phenomenon: Voices of Students With Written Language Disorders - Grigienė, Ieva; Galkienė, Alvyra (Pedagogika, 2024)
Adopting a phenomenological approach, this study analyses the “children’s voice” which reveals how children experience the defining experiences of a written language disorder and gives meaning to the phenomenon of mutual support. The results of the study present the components of the mutual support phenomenon, through which the interpretation of their understanding is revealed: being empathetic, seeking recognition in the community, modelling learning activities, interpreting learning support.